A new dimeric sesquiterpene and other related derivatives from the marine red alga Laurencia okamurai. (August 2018) - Yang, Xin-Xin; Su, Yong-Zheng; Tan, Ji; Cai, Chun-Er; He, Pei-Min; Jia, Rui
Abstract: A new Bis-sesquiterpene, Nanji A (1 ), has been isolated together with 7 known compounds, debromolaurinterol (2 ), laurinterol (3 ), laurinterol acetate (4 ), isolaurinterol (5 ), 3α-hydroperoxy-3-epiaplysin (6 ), 3β-hydroperoxyaplysin (7), Laurokomurenene A (8 ), from the Nanji red alga Laurencia okamurai . The structure of1 was elucidated on the basis of extensive spectroscopic analysis of its EIMS, 1D and 2D NMR data. Furthermore, the chemotaxonomic significance of these compounds was also summarized. Highlights: A new dimeric sesquiterpene, Nanji A (1 ) together with 7 known compounds (2 –8 ) has been isolated from the Nanji red alga Laurencia okamurai . Nanji A presents the fourth example of a rare dimeric sesquiterpene of the cyclolaurane-type, which has been reported from Laurencia microcladia . Nanji A is isolated from Laurencia okamurai for the first time.